An Analysis of the relationship between EU sovereign and bank CDS spreads (pre and post the global financial crisis) - Wu, Ting-Ting (2016)
This study investigates the influence of banking industry on sovereign CDS spread change, and investigates the domestic and global financial sectors effects in European Union area. In this research, we apply monthly data from January 2005 to December 2014, and separate these data into three time periods, 2005-June 2007, July 2007-2009, and 2010-2014, to see whether their effects are different before and after financial crisis. We find that sovereign CDS spreads are depended on their last prices during the whole period, while the impact of bank CDS spread is only statistic significant in the last two period. The effect of foreign bank subsidiaries entries is significant in the first and the last period but with opposite sign. In addition, after robust by dummy variable, it shows a strong significant impact on EU countries’ sovereign CDS spreads during the second period. As to other local and global financial indicators, all of them present an insignificant result in the pre-crisis period. GDP growth and debt-to-GDP ratio becomes significant after July 2007 showing local economies developing and fiscal policies are getting important, whereas VIX index only shows itself significant in the crisis period presenting that EU members are affected by global volatility during the financial crisis.